Household Vulnerability on the Frontline of Climate Change: The Pacific Atoll Nation of Tuvalu - Tauisi Taupo; Harold Cuffe; Ilan Noy (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper investigates the vulnerability of households to climatic disasters in the low-lying atoll nation of Tuvalu. Small Island Developing States, particularly the atoll islands, are considered to be the most vulnerable to climatic change, and in particular to sea-level rise and its associated risks. We construct poverty and hardship profiles for households on the different islands of Tuvalu, and combine these with geographic and topographic information to assess the exposure differentials among different groups using spatial econometric models. Besides the observation that poor households are more vulnerable to negative shocks because they lack the resources to respond, we also find that they are also more likely to reside in highly exposed areas to disasters (closer to the coasts and at lower elevation) and have less ability to migrate (between and within the islands).
Keywords: C31; I30; Q54; Q56; 330; vulnerability; exposure; poverty; hardship; Tuvalu; atoll